Rāingān phon kāndamnœ̄nkān tām nayōbāi khō̜ng khana ratthamontrī ratthabān Phon ʻĒk Surayut Čhulānon (Samnakngān Khana Kammakān Phatthanā Kānsētthakit læ Sangkhom hǣng Chāt : Samnak Lēkhāthikān Nāyok Ratthamontrī : Samnak Lēkhāthikān Khana Ratthamontrī, 2007)
Report on national development process of Thai Government under 24th Prime Minister, Surayut Chulanon.